2018
DOI: 10.1021/acsami.8b08888
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Cu9S5 as a Hole Transport Layer for Efficient and Stable Perovskite Solar Cells

Abstract: Organic-inorganic perovskite solar cells have seen tremendous developments in recent years. As a hole transport material, 2,2',7,7'-tetrakis( N, N-di- p-methoxyphenylamine)-9,9'-spirobifluorene (Spiro-OMeTAD) is widely used in n-i-p perovskite solar cells. However, it may lead to the perovskite film degradation due to the dopant lithium bis((trifluoromethyl)sulfonyl)amide (Li-TFSI), which has strong hydrophilicity. CuS is considered as a superior p-type transport material, which also has a favorable energy lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
(46 reference statements)
0
26
0
Order By: Relevance
“…From the KPFM test and the reported band structure of Cu 9 S 5 , the band diagrams of Cu 9 S 5 /MoS 2 is drawn in Figure f. It can be seen that a Type‐II contact is formed between Cu 9 S 5 and MoS 2 , which facilitates the charge separation and transfer in the p‐n junction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the KPFM test and the reported band structure of Cu 9 S 5 , the band diagrams of Cu 9 S 5 /MoS 2 is drawn in Figure f. It can be seen that a Type‐II contact is formed between Cu 9 S 5 and MoS 2 , which facilitates the charge separation and transfer in the p‐n junction.…”
Section: Resultsmentioning
confidence: 99%
“…The optical bandgap of one nanomaterial is deeply linked with its morphology. The reported bandgap of Cu 9 S 5 varied from 1.73 eV (film) to 1.93 eV (nanocube) and 2.5 eV (bulk) . Therefore, to make clear the bandgap of the synthesized Cu 9 S 5 nanoflakes, we conducted photoluminescence (PL) and micro‐area absorption measurements on a single nanoflake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al reported organic‐inorganic hybrid HTL which was composed of the unhoped spiro‐OMeTAD and Cu 9 S 5 layer . The modified hole and electron transport layers were applied in n–i–p perovskite solar cells.…”
Section: Influence Of Charge Transport Layer On Stabilitymentioning
confidence: 99%
“…Lei et al assembled PSCs based on a doped Spiro-OMeTAD/Cu 7.5 S double layered HTM by vacuum thermal evaporation of CuS powders, reaching a PCE of 17.91% [28]. Very recently, Han et al fabricated a planar PSC with an undoped Spiro-OMeTAD/ Cu 9 S 5 double layered HTM and nitrogen doped SnO 2 ETL, achieving a maximum PCE of 17.10% [29]. Cu 9 S 5 was proven to be a superior HTL and electrode interface modification layer in both polymer and PSC solar cells [29,30].…”
Section: Introductionmentioning
confidence: 99%